Improving Grade V Students' Cooperation Skills by Using the Team Quiz Learning Model - Nadila, Putri; Alim, Melvi Lesmana; Joni, Joni (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
This study is motivated by the insufficient level of students’ cooperative skills in Pancasila Education at Class V UPT SDN 003 Muara Uwai, as reflected in weak communication, limited team contribution, and inadequate recognition of individual learning differences. To address this issue, the study implemented the team quiz learning model as an instructional strategy for improving students’ cooperative skills in learning the topic “My Country, Indonesia.” This research employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of two meetings and four stages: planning, implementation, observation, and reflection. The study involved 10 Class V students, comprising five boys and five girls. Data were collected through observation and documentation. The findings show that students’ cooperative skills increased from 30% before the intervention to 50% in the first cycle and further improved to 80% in the second cycle. These results indicate that the team quiz learning model effectively enhances students’ cooperative skills in Pancasila Education. The study contributes to elementary education practice by demonstrating that interactive, team-based learning can strengthen students’ communication, participation, and collaborative responsibility in civic learning contexts.